Income Distribution, Factor Endowments, and Trade Revisited: The Role of Non-Tradable Goods - Galiani, Sebastian (2017)
We return to the traditional theme of the distributive consequences of international prices and trade policies, focusing on economies relatively abundant in natural resources with a large non-tradable-goods sector. Changes in international prices create an aggregate demand effect which impacts on the earnings of factors employed in the non-traded goods sector. We show that, in economies highly specialized in the production of tradable goods and where the import-competing sector is small, under standard assumptions, terms-of- trade shifts have a neutral effect on factor prices and thus lack distributive effects, quite differently from Stolper-Samuelson scenarios. In economies with sizable import-competing sectors and two ?urban? productive factors (e.g. skilled and unskilled labor), changes in the terms of trade do induce distributional tensions through two channels: (i) the exogenous shift in the relative price of tradable goods, and (ii) the endogenous displacement of the demand for non-tradables. We illustrate how, according to the structure of the economy, different patterns of income distribution may arise. Next, we analyze the introduction of trade duties. Trade taxes change relative prices between tradable goods as a terms-of-trade shock does, but also introduce an additional demand mechanism, that depends on the use the government gives to the revenues. If the tax revenues are transferred back to the private sector, the resulting reallocation of spending favors those factors used intensively in the production of non-tradables.